Clinical Practice Guidelines: Diagnostic and Treatment of Multiple Sclerosis in Adults - Vizcarra, Darwin R. (2019)
Multiple Sclerosis (MS) is a chronic disease of the central nervous system, for which there is still no definitive cure; but there is a diverse variety of therapies with the objective of modifying the course of the disease, which promotes the constant inclusion of new therapeutic strategies. Objective: The Peruvian Society of Neurology, as requested by the Peruvian Health Ministry, convened a committee of experts with the purpose of elaborating a clinical practice guideline for the diagnosis and treatment of MS. Method: Clinical practice guidelines were searched and evaluated according to the AGREE II methodology, choosing the Catalan Clinical Practice Guide as a model. The clinical questions not related to treatment were solved through a systematic review. The clinical treatment questions were assessed under the PICO format and were solved with a meta-analysis of clinical trials available until August 2017, considering the therapies approved by DIGEMID until January 2017. The final recommendations were elaborated using the modified Delphi method with a consensus of at least 80% of the members of its committee. Finally, an external revision of the manuscript was made by international experts in MS. Results: Eighteen clinical questions and twenty-one recommendations for management were developed, including therapeutic algorithms.